Nodular hypertrophy of the external nose (Rhinophyma). Own observation - Lewandowski, Bogumił; de Sternberg Stojałowski, Sebastian (European Journal of Clinical and Experimental Medicine, 2026)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Rhinophyma is a late manifestation of rosacea. Nodular hypertrophy of the external nose is a chronic disease lasting for many years. Rosacea itself is a frequent disease most common among women, yet its manifestation resulting in rhinophyma is typical for men in their 50s and 60s. The etiopathogenesis of rosacea is complex and not yet investigated thoroughly. Early stages are characterized with disruption of microcirculation in the nose and hypertrophy of sebaceous glands. Over the years skin and subcutaneous tissues proliferate and become fibrous leading to enlargement and malformation of the nose. Lesions pose not only a cosmetic defect, but may also cause obstruction to the nasal passage. Between 1992 and 2013 five patients who presented with rhinophyma were treated at the Clinical Department of Maxillo-Facial Surgery of Provincial Specialist Hospital in Rzeszów. A case study of a patient who was recently treated at the clinic is presented below